ln (2x-1) = 3

2 Answers | Add Yours

hala718's profile pic

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted on

ln (2x-1) = 3

We coudl rewrite ln x=y as  x= e^y

==> 2x-1 = e^3

 Now add 1 to both sides:

==> 2x = e^3 + 1

Now divide by 2:

==> x = (e^3 + 1)/2

==>  x = 10.54 (approx.)

neela's profile pic

neela | High School Teacher | (Level 3) Valedictorian

Posted on

ln(2x-1) =3

To solve  this we go for the antilogarithm on both sides.

2x-1 = e^3 by definition.

2x= e^3+1

x  = (e^3+1)/2

We’ve answered 334,087 questions. We can answer yours, too.

Ask a question